Evaluating the Concentration of a Candida albicans Suspension - Rodrigues, Acácio (Hindawi Publishing Corporation, 1993)
Objective: The objective of this study was to develop a reproducible method of establishing the concentration of yeast cells per milliliter of solution. Methods: Three methods of determining the number of yeast cells in solution were compared: Neubauer's counting chamber, spectrophotometry, and nephelometry. Results: All three methods were comparable and reproducible. The following formulas were highly effective in determining the number of yeast cells in solution: chamber (× 10(3)/ ml) 64.3 + 8,206 × spectrophotometry (absorbance); and chamber (× 10(3) /ml) –0.2 + 64 × nephelometry (volt). Conclusions: Utilization of spectrophotometry or nephelometry and the appropriate formula allow for the precise determination, which is easily reproducible, of the concentration of yeast cells in solution. This will facilitate experimentation involving precise inocula or requirement for specific concentrations of yeast cells for various experiments.